Development of gas density measurement model (tank) based on principal component analysis (PCA) technique - Wan Mohd Hidayat, Wan Abdullah (2006)
The real importance of controlling gas density is based on the fact that it contributes significantly to the composition of the gas being controlled. Even with small variations can cause significant process upsets if not adequately controlled due to changing in composition. This research purposely to develop a model of gas density measurement as the process instrument nowadays hardly to correlate simultaneously the input variables to the output variables. In this respect, density is known as output whereby it depends on other variables (input) which are pressure and temperature of the given process. In other words, all variables which can be directly measured and contribute to the primary variables are known as 'secondary variables'. Thus, the Principal Component Analysis (PCA) approach is used plus the MATLAB programming to ensure the gas density measurement model is valid as the real process. At the end of this research, the developed model can be used to identify the best configurations of inputs variables in producing the specified output that intended. The best outcome is the effect of temperature and pressure to the density is very significant as the relationships between those variables are proportional to each other.